Longer lactation duration is associated with decreased prevalence of non-alcoholic fatty liver disease in women - Ajmera, Veeral H. (J Hepatol, 2018)
BACKGROUND & AIMS: Lactation lowers blood glucose and triglycerides, and increases insulin sensitivity. We hypothesized that a longer duration of lactation would be associated with lower prevalence of non-alcoholic fatty liver disease (NAFLD), which is the leading cause of chronic liver disease in the United States. METHODS: Participants from the Coronary Artery Risk Development in Young Adults cohort study who delivered ≥ 1 child post-baseline (Y0: 1985–1986), and underwent CT quantification of hepatic steatosis 25 years following cohort entry (Y25: 2010–2011) were included (n = 844). The duration of lactation was summed for all post-baseline births, and NAFLD at Y25 was assessed by central review of CT images and defined by liver attenuation ≤ 40 Hounsfield Units after exclusion of other causes of hepatic steatosis. Unadjusted and multivariable logistic regression analyses were performed using an a priori set of confounding variables; age, race, education, and baseline body mass index. RESULTS: Of 844 women who delivered after baseline (48% black, 52% white, mean age 49 years at Y25 exam), 32% reported lactation duration of 0 to 1 month, 25% reported >1 to 6 months, 43% reported more than 6 months, while 54 (6%) had NAFLD. Longer lactation duration was inversely associated with NAFLD in unadjusted logistic regression. For women who reported >6 months lactation compared to those reporting 0–1 month, the odds ratio for NAFLD was 0.48 (95% Cl 0.25–0.94; p = 0.03) and the association remained after adjustment for confounders (adjusted odds ratio 0.46; 95% Cl 0.22–0.97; p = 0.04). CONCLUSIONS: A longer duration of lactation, particularly greater than 6 months, is associated with lower odds of NAFLD in midlife and may represent a modifiable risk factor for NAFLD.